Identification and characterization of stem cell secretome-based recombinant proteins for wound healing applications - Kim, Ji Hyun; Green, Denethia S.; Ju, Young Min; Harrison, Mollie; Vaughan, J. William; Atala, Anthony; Lee, Sang Jin; Jackson, John D.; Nykiforuk, Cory; Yoo, James J. (Frontiers in Bioengineering and Biotechnology, 2022)
Stem cells have been introduced as a promising therapy for acute and chronic wounds, including burn injuries. The effects of stem cell-based wound therapies are believed to result from the secreted bioactive molecules produced by stem cells. Therefore, treatments using stem cell-derived conditioned medium (CM) (referred to as secretome) have been proposed as an alternative option for wound care. However, safety and regulatory concerns exist due to the uncharacterized biochemical content and variability across different batches of CM samples. This study presents an alternative treatment strategy to mitigate these concerns by using fully characterized recombinant proteins identified by the CM analysis to promote pro-regenerative healing. This study analyzed the secretome profile generated from human placental stem cell (hPSC) cultures and identified nine predominantly expressed proteins (ANG-1, FGF-7, Follistatin, HGF, IL-6, Insulin, TGFβ-1, uPAR, and VEGF) that are known to contribute to wound healing and angiogenesis. These proteins, referred to as condition medium factors (CMFs), were used in combination to test the effects on human dermal fibroblasts (HDFs). Our results showed that CMF treatment increased the HDF growth and accelerated cell migration and wound closure, similar to stem cell and CM treatments. In addition, the CMF treatment promoted angiogenesis by enhancing new vessel formation. These findings suggest that the defined CMF identified by the CM proteomic analysis could be an effective therapeutic solution for wound healing applications. Our strategy eliminates the regulatory concerns present with stem cell-derived secretomes and could be developed as an off-the-shelf product for immediate wound care and accelerating healing.